Positive coping with retirement among retired teachers in Makueni County - Musila, Annastasia Katee (Advances in Social Sciences Research Journal, 2019)
ABSTRACT This paper is based on an ongoing PhD study, it looks at the adaptive ways that retired teachers in Makueni County applied in adjusting to their retirement. Retirement is a period that has been associated with a myriad of problems ranging from physical, psychological to socio-economic ones. A number of researches in Kenya have focused on the challenges of retirement however limited studies have examined how retirees contend with retirement. This study sought to find out how retired teachers in Makueni County were adjusting in their retirement in spite of the challenges associated with this period. The study was guided by the following theories: Social Construction Theory by Berger (1966), Disengagement Theory by Cumming and Henry (1961) and Life Cycle Perspective by Elder Jr (1960).The research sample consisted of 249 respondents (173 males and 76 females) who were selected through purposive and snow ball sampling techniques. Moreover, questionnaires, face to face interviews and focus group discussions were used to collect data. Qualitative data was thematically coded and analysed through content narrative analysis while Statistical Package for the Social Science (SPSS) was used in getting simple tables. The research concludes that retirement is a time of freedom when retirees can invest their time, wealth and energy constructively in ways that bring prosperity to themselves and the society. The study recommends that employers need to continually train workers in preparation for retirement, and pension should be paid in time.